2018
DOI: 10.5114/hivar.2018.76371
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality of life and its associated factors among people living with HIV/AIDS

Abstract: Introduction: Acquired immunodeficiency syndrome (AIDS) has evolved from a mysterious illness to a global pandemic which has infected tens of millions of people. Assessing health-related quality of life (HQOL) is useful for documenting the patients' perceived burden of chronic disease, tracking changes in health over time, assessing the effects of treatment and quantifying the return on health care investment. The study aimed to assess the quality of life and its associated factors in patients with HIV/AIDS. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
2
2
Order By: Relevance
“…However, this score was lower compared to the results reported by Palwe et al. (2018) with a mean score of 13.28 ± 3.97 and Liping et al. (2015) with a mean score of 15.99 ± 2.91.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…However, this score was lower compared to the results reported by Palwe et al. (2018) with a mean score of 13.28 ± 3.97 and Liping et al. (2015) with a mean score of 15.99 ± 2.91.…”
Section: Discussioncontrasting
confidence: 70%
“…This study showed that the LS and QOL in patients with HIV/AIDS were lower comparing to other studies (Jain & Tiwari, 2016; Liping, Peng, Haijiang, Lahong, & Fan, 2015; Mudgal & Tiwari, 2015b; Palwe et al., 2018).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Our study showed that QOL in PLWH was lower among PLWH in other countries [ 31 , 32 ]. In many studies, poor QOL was associated with a lower immune response, non-adherence, poor mental health, and greater disease severity [ 8 , 33 ].…”
Section: Discussionmentioning
confidence: 64%